ROLE OF APOPTOSIS IN AIRWAY EPITHELIUM - Alenzi, Faris Q (Pakistan Journal of Physiology, 2009)
Background: Airway epithelial cells may play an important clinical role in the apoptosis of eosinophils. To study recognition pathways, two types of large bronchial airway epithelial cells were used (LAECs and A549). Methods: Both resting, and dexamethasone-stimulated epithelial cells, were used in an inhibition assay. Confocal microscopy was used to demonstrate engulfment of apoptotic eosinophils. Apoptotic eosinophils were recognized and phagocytosed by macrophages, and by LAECs. Results: The ability of LAECs to engulf apoptotic eosinophils was enhanced by dexamethasone and interlukin-1 (IL-1Î²). Inhibition by monoclonal antibodies (Mabs) prevented the uptake of apoptotic cells by LAECs. Conclusion: This study therefore suggests that LAECs are capable of recognizing and engulfing apoptotic eosinophils, and that this process is enhanced by IL-1Î² and dexamethasone